Impact of early remission by induction therapy on allogeneic stem cell transplantation for acute myeloid leukemia with an intermediate‐risk karyotype in first complete remission. (11th October 2014) - Hemmati, Philipp G.; Terwey, Theis H.; Na, Il‐Kang; le Coutre, Philipp; Jehn, Christian F.; Vuong, Lam G.; Dörken, Bernd; Arnold, Renate
Abstract For patients with acute myeloid leukemia (AML) early achievement of remission during induction treatment is an important predictor for long‐term outcome irrespective of the type of consolidation therapy employed. Here, we retrospectively examined the prognostic impact of early remission (ER) vs. delayed remission (DR) in a cohort of 132 AML patients with an intermediate‐risk karyotype undergoing allogeneic stem cell transplantation (alloSCT) in first complete remission (CR1). In contrast to patients showing DR, patients achieving ER had a significantly higher 3‐yr overall survival (OS) and disease‐free survival (DFS) of 76% vs. 54% (P = 0.03) and 76% vs. 53% (P = 0.03). Likewise, 3 yr after alloSCT the cumulative incidence of relapse (CI‐R) was significantly lower in the ER subgroup as compared to patients achieving DR, that is, 10% vs. 35% (P = 0.004), whereas non‐relapse mortality (NRM) did not differ significantly. Multivariate analysis identified DR as an independent prognosticator for an inferior DFS (HR 3.37, P = 0.002) and a higher CI‐R (HR 3.55, P = 0.002). Taken together, these data may indicate that the rapid achievement of remission predicts a favorable outcome in patients with intermediate‐risk AML undergoing alloSCT in CR1. In turn, the adverse effect of DR may not be fully overcome by alloSCT.